REASONS FOR EDUCATIONAL RETARDATION OF STUDENTS IN SECONDARY SCHOOL FROM THE POINT OF VIEW OF TEACHERS - Sadq Jafer Hassan Salman (European Journal of Humanities and Educational Advancements, 2023)
Students who are educational retardation are part of this society’s real wealth. They are part of the society and study their problems. It requires attention at all times and needs individual and collective attention. Students educational retardation suffer a study of behavioral problems and psychological disorders including the emergence of feelings of frustration inherent in the behavior of students, such as those appearing in aggressive behavior against peers and out of the system and other behaviors. In order to find out the reasons for the educational retardation in secondary school students, a measure was adopted (Nisreen Tawfiq Ibrahim Zaher, 2019), which aims to Measuring the reasons for the educational retardation pupils. The study sample consisted of (138) students, and (138) teachers were withdrawn to answer the research tool. After selecting the research sample and distributing the research tool, the researcher analyzed the responses of the sample members obtained on the scale. The results of the research show that the reason for the educational retardation in secondary school students is mainly due to reasons educational retardation to the student himself and then the second reason for the educational retardation of the school methods of teaching and education applied within the school, while the last reason for the educational retardation in school are the family and social problems facing the student During his studies